Developing Human Capital for Food Safety: Global Best Practices and Policy Lessons for Azerbaijan - Garashli, Susan; Khidirzada, Nazrin; Gasimova, Seljan (ADA University, 2025)
This paper explores the shortage of skilled food safety professionals in Azerbaijan and assesses available policy alternatives to close the human capital gap prevalent in this sector. To do so, the study relies on qualitative research methods, including in-depth interviews with representatives from the Azerbaijan Food Safety Agency (AFSA) and the Azerbaijan Food Safety Institute (AFSI), and defines key challenges to the problem at hand in terms of 3 problems leading up to a larger problem of shortage: lack of relevant educational programs, lack of progress in learning new practical skills, and the lack of institutional human resource development conducive to career growth and employee retention. Three policy options were evaluated using five criteria: effectiveness, efficiency, equity, feasibility, and flexibility. The analysis concluded that the most sustainable and impactful solution lies in establishing specialized undergraduate and graduate programs in Azerbaijani universities that meet international standards. This solution addresses the shortage while also offering a high return on investment, enhancing institutional capacity, and reducing the reliance on external support. The paper also provides actionable recommendations such as initiating more partnerships to design practical curricula, focusing on teaching global trends and standards, and providing extra funding for modernization of the study environment and facilities in support of the implementation of this policy.
Keywords: Food safety -- Government policy -- Azerbaijan.; Food industry and trade -- Safety regulations -- Azerbaijan.; Human capital -- Development -- Azerbaijan.; Manpower policy -- Azerbaijan.; Higher education -- Curricula -- Azerbaijan.